Global Supply Chain Management: Toward a Theoretically Driven Research Agenda. (31st July 2013) - Connelly, Brian L.; Ketchen, David J.; Hult, G. Tomas M.
<x xml:space="preserve">Abstract</x> As competition becomes increasingly global in nature, the importance of global supply chain management grows. Yet, research attention on this matter has been limited. We seek to offer a strong foundation for future research on global supply chain management by examining it from the perspectives of six prominent organizational theories that range in emphasis from primarily endogenous to primarily exogenous influences. We, in turn, apply real options theory, internationalization theory, organizational economics, resource dependence theory, social network theory, and institutional theory. We also examine the implications for global supply chain management of juxtaposing the insights provided by multiple theories. Our hope is that the ideas generated by applying these theories set the stage for subsequent theoretically robust investigations of global supply chain management.